Social Vulnerability and Frailty in Hospitalized Older Adults. - Mah, Jasmine C.; Godin, Judith; Stevens, Susan J.; Keefe, Janice M.; Rockwood, Kenneth; Andrew, Melissa K. (Canadian Geriatrics Journal, 2023)
Background Social vulnerability is the accumulation of disadvantageous social circumstances resulting in susceptibility to adverse health outcomes. Associated with increased mortality, cognitive decline, and disability, social vulnerability has primarily been studied in large population databases rather than frail hospitalized individuals. We examined how social vulnerability contributes to hospital outcomes and use of hospital resources for older adults presenting to the Emergency Department. Methods We analyzed patients 65 years of age or older admitted through the Emergency Department and consulted to internal medicine or geriatrics at a Canadian tertiary care hospital from July 2009 to September 2020. A 20-item social vulnerability index (SVI) and a 57-item frailty index (FI) were calculated, using a deficit accumulation approach. Outcomes were length of stay (LOS), extended hospital LOS designation, alternative level of care (ALC) designation, in-hospital mortality, and discharge to long-term care (LTC). Results In 1,146 patients (mean age 80.5±8.3, 54.0% female), mean SVI was 0.40±0.16 and FI was 0.44±0.14. The SVI scores were not associated with admission to hospital. Amongst those admitted, for every 0.1 unit increase in SVI, LOS increased by 1.15 days (p<.001) after adjusting for age, sex and FI. SVI was associated with staying over the expected LOS (aOR: 1.19, 1.05-1.34, p=.009) and ALC status (aOR 1.39, 1.12-1.74, p<.004). SVI was not associated with in-hospital mortality, but was associated with incident discharge to LTC (aOR 1.03, 1.02-1.04, p<.001). Conclusion Independent of frailty, being socially vulnerable was associated with increased LOS, designation as ALC, and being discharged to LTC from hospital. Consideration of social vulnerability's influence on prolonged hospitalization and long-term care needs has implications for screening and hospital resources.